Activity learning : discovering, recognizing, and predicting human behavior from sensor data - Cook, Diane J., 1963- (Hoboken, NJ : Wiley, 2015)
"The book provides an in-depth look at computational approaches to activity learning from sensor data"--
Machine generated contents note: 1 Introduction 2 Activities 2.1 Definitions 2.2 Classes of Activities 2.3 Additional Reading 3 Sensing 3.1 Sensors Used for Activity Learning 3.2 Sample Sensor Datasets 3.3 Features 3.4 Multisensor Fusion 3.5 Additional Reading 4 Machine Learning 4.1 Supervised Learning Framework 4.2 Naïve Bayes Classifier 4.3 Gaussian Mixture Model 4.4 Hidden Markov Model 4.5 Decision Tree 4.6 Support Vector Machine 4.7 Conditional Random Field 4.8 Combining Classifier Models 4.9 Dimensionality Reduction 4.10 Additional Reading 5 Activity Recognition 5.1 Activity Segmentation 5.2 Sliding Windows 5.3 Unsupervised Segmentation 5.4 Measuring Performance 5.5 Additional Reading 6 Activity Discovery 6.1 Zero-Shot Learning 6.2 Sequence Mining 6.3 Clustering 6.4 Topic Models 6.5 Measuring Performance 6.6 Additional Reading 7 Activity Prediction 7.1 Activity Sequence Prediction 7.2 Activity Forecasting 7.3 Probabilistic Graph-Based Activity Prediction 7.4 Rule-Based Activity Timing Prediction 7.5 Measuring Performance 7.6 Additional Reading 8 Activity Learning in the Wild 8.1 Collecting Annotated Sensor Data 8.2 Transfer Learning 8.3 Multi-Label Learning 8.4 Activity Learning for Multiple Individuals 8.5 Additional Reading 9 Applications of Activity Learning 9.1 Health 9.2 Activity-Aware Services 9.3 Security and Emergency Management 9.4 Activity Reconstruction, Expression and Visualization 9.5 Analyzing Human Dynamics 9.6 Additional Reading 10 The Future of Activity Learning Appendix: Sample Activity Data Bibliography.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Active learning -- Data processing; Detectors -- Data processing; Multisensor data fusion; TECHNOLOGY & ENGINEERING / Electronics / Digital; TECHNOLOGY & ENGINEERING / Sensors; COMPUTERS / Database Management / Data Mining; Electronic books; Electronic books